Effective injury prevention in soccer - Kirkendall, D. T.; Dvorak, J. (The Physician and Sportsmedicine, 2010)
Sports participation is accompanied by risk of injury, and each specific sport has its own unique injury profile. One of the goals of a sports medicine professional is injury prevention, and the past decade has seen numerous reports on the outcomes of injury-prevention studies. Health care professionals have been particularly vigilant in attempting to reduce common injuries in soccer, beginning with work in the early 1980s to the rigorous randomized trials of today. The use of a structured, generalized warm-up program has been shown to be effective in preventing common soccer injuries, reducing overall injury rates by approximately 30%. Given the number of individuals who play soccer worldwide, any injury reductions will likely have an impact on public health. It is an important goal of the sports medicine community to inform physicians and other sports medicine professionals about the effectiveness of prevention programs to increase use and compliance.